Increased wait-list time predicts dropout from outpatient enhanced cognitive behaviour therapy (CBT-E) for eating disorders - Carter, O.; Pannekoek, Linda; Fursland, A.; Allen, K.; Lampard, Amy; Byrne, S. (Elsevier Ltd, 2012)
Between 30 and 70% of patients with eating disorders drop out from outpatient treatment. However, research has been unable to identify factors that consistently predict dropout from eating disorder treatment. Most studies have exclusively investigated the role that individual patient characteristics play in dropout and have ignored more process-based factors such as expectations about treatment, the therapeutic alliance, or time spent on a treatment waiting list. This study aimed to investigate the roles of both individual patient characteristics and process-based factors in dropout from outpatient treatment or eating disorders. The study involved data collected from consecutive eating disorder referrals to the only public specialist eating disorder service for youth and adults in Perth, Western Australia. The standard treatment provided at this service is Enhanced Cognitive Behaviour Therapy on an individual basis. The study involved 189 patients referred to the service between 2005 and 2010. Forty five percent of this sample dropped out of treatment. Results showed that, in this sample, two individual factors, lowest reported weight and the tendency to avoid affect, and one process-based factor, time spent on the wait list for treatment, were significant predictors of dropout. These findings are valuable because a process-based factor, such as wait-list time, may be easier to address and modify than a patient’s weight history or the trait of mood intolerance. Increased resources for eating disorder services may reduce waiting list times which would help to reduce dropout and maximize treatment outcomes.